Доля волинських адвокатів на початку Другої світової війни (за матеріалами архівно-кримінальних справ) - Сущук, Оксана Петрівна; Sushchuk, Oksana (Східноєвропейський національний університет імені Лесі Українки, 2016)
На підставі аналізу архівно-кримінальних справ репресованих досліджено біографії волинських адвокатів на початку Другої світової війни, з’ясовано особливості впровадження радянського режиму на Волині та застосування репресивних заходів до його ймовірних опонентів.On the basis of analysis of archival criminal cases investigated repressed biography Volyn lawyers at the beginning of the Second World War. Clarify the features of the formation of the Soviet regime in the Volyn region, the use of repressive measures against its possible opponents. Attention is drawn to the fact that key reforms process started, the main instrument of instruction of local people to the path of socialism became a mass political terror. It is proved that the lawyers as the most educated and politically active members of society, have become one of the first objects of repression by the new Soviet regime.
The Fate of the Volyn Lawyers at the Beginning of World War II (According to Archival Criminal Cases)
Keywords: адвокат; репресії; НКВС; Волинь; Ю. Загурський; М. Керер; А. Станевич; Г. Степура; С. Підгірський; реабілітація; lawyer; repression; Volyn; J. Zagursky; M. Kerer; A. Stanevych; G. Stepura; S. Pidgirsky; rehabilitation